Physiological and Transcriptional Responses to Acute and Chronic Thermal Stress in the Ark Shell Scapharca subcrenata - Zou, Desheng; Ning, Junhao; Lu, Xia; Wang, Xia; Chen, Min; Liu, Bo; Fang, Jun; Wang, Chunde (Frontiers in Marine Science, 2021)
Ark shells (Scapharca subcrenata) grown on the tidal flats are often exposed to high temperature stresses in summers. In order to better understand their adaption to extreme or natural high temperature, herein we investigated their physiological and transcriptional responses to acute or chronic thermal stress at 32 ℃ (close to 96-h upper median lethal temperature). A significantly higher cumulative mortality (52% in 96 h) was observed in the acute heating treatment (AHT) group than that (22% in 7 days) in the chronic heating treatment (CHT) group. The apoptosis and necrosis rates of haemocytes were increased significantly in a time-dependent manner under both thermal stress strategies. Activities of antioxidant enzymes (SOD and CAT) increased dramatically in a short time followed by a quick decline and reached to a lower level within 12 h in the AHT group, but maintain relatively high levels over a long period in the CHT group. The contents of MDA were increased significantly firstly and restored to the original later in both acute and chronic thermal stress. Moreover, expression of the genes related to heat shock proteins (HSP90, HSP70, HSP20 and sHSP), apoptosis (TRAF6, GRP78, and Casp-3) and antioxidant responses (GST and MRP) could be induced and up-regulated significantly by thermal stress, however, expression of RGN, MT and PRX was down-regulated dramatically under the two heating treatments. These results suggested that anti-apoptotic system, antioxidant defense system and heat shock proteins could play important roles in thermal tolerance of ark shells, and the heat-resistant ark shell strains could be selected continuously by properly chronic thermal stress.